Effects of orthognathic surgery with maxillary impaction plus septoplasty and total turbinectomy on breathing (Research, Society and Development, 2022)
Complete removal of hypertrophied inferior nasal turbinates may favour the occurrence of the empty nose syndrome (ENS). Some surgeons recommend partial turbinectomy in order to minimize the occurrence of ENS. However, little is known about whether total removal of the inferior nasal turbinate is associated with ENS. The aim of the present study was to evaluate the effects of total turbinectomy and septoplasty on the breathing of individuals undergoing orthognathic surgery with maxillary impaction. A total of 20 individuals participated in this cross-sectional study, in which the relationship between exposure (maxillary orthognathic surgery) and outcome (nasal respiratory function) was investigated. The Empty Nose Syndrome 6-Item questionnaire and Nasal Obstruction Symptom evaluation scale were applied to investigate the ENS. A three-dimensional assessment of the piriform opening was performed pre- and postoperatively by computed tomography in order to measure the volume of the nasal cavities using the Dolphin Imaging software. ENS was detected in 35% of patients, while 13 reported improved breathing. Symptoms of ENS such as dryness, suffocation, nose feels too open and nasal crusting were mentioned. The mean nasal cavity volume was 7477.15 mm³ greater in the initial evaluation (p